Sorbitol induces flavonoid accumulation as a secondary signal via the nanoencapsulated SPc/lncRNA809-MmNAC17 module against Alternaria alternata in Malus micromalus - Tingting Du; Dong Meng; Hongyan Cao; Yi Lian; Rui Wu; Tengyue Liu; Tianyi Wang; Cai Qin; Zhihua Song; Biying Dong; Yujie Fu; Qing Yang (Molecular Horticulture)
Abstract Sorbitol is an important primary metabolite that serves as both a carbon source and signal to pathogens. The leaf diseases caused by Alternata alternata are particularly serious in crabapple (Malus micromalus). Here, we found that sorbitol can enhance the resistance of crabapple to A. alternata R1 by increasing the content of flavonoid catechin. Nanomaterials as an emerging technology tool can efficiently deliver lncRNA to target cells. Here, we found nanoencapsulated lncRNA809 (SPc/lncRNA809) exhibits significant resistance to R1strain. To elucidate the effect of SPc/lncRNA809 on flavonoids catechin synthesis, we observed the expression of lncRNA809 was consistent with that of MmNAC17 which regulates the synthesis of catechin and both could jointly respond to sorbitol. MmNAC17 induced the accumulation of catechin in vivo by directly activating the expression of catechin synthase genes MmF3H and MmLAR. Correspondingly, overexpression of lncRNA809 significantly upregulated the expression of MmNAC17 and enhanced the disease resistance. This study reveals for the first time that sorbitol positively regulates the expression of MmNAC17 through lncRNA809, promoting the accumulation of catechin via the expression of MmF3H and MmLAR, ultimately improving the defense response of M. micromalus. This research provides a crucial foundation for the establishment and application of sorbitol-based signaling regulatory networks.